Decomposing social groups differential in stunting among children under five in India using nationally representative sample data - Mriganka Dolui; Sanjit Sarkar (Scientific Reports)
Abstract Stunting among children is a reflection of the chronic malnutrition caused by a complex set of behavioural, demographic, and socioeconomic factors. This long-term detrimental exposure to chronic malnutrition is disproportionately higher among social and economically deprived groups, leading to significant differentials in the prevalence of stunting across various social strata. Therefore, this study investigates the inequality of social groups in terms of the prevalence of stunting across Schedule Caste (SC)-Scheduled Tribe (ST) and non-SC-ST. The study used 1,93,886 children’s data aged 0–59 months from the recent round of the National Family Health Survey. Descriptive statistics, multivariable logistic regression, F-test, t-test and chi-squared (χ²) test were applied to understand the prevalence, determinants, and associations, respectively. The Fairlie decomposition model was applied to quantify the factors contributing to the inequality of stunting across social groups. The results revealed that the prevalence of stunting was higher among SC-ST (39.60%) children compared to non-SC-ST (33.27%). In addition, children aged 15–30 months (AOR: 1.895, 95% CI: 1.843–1.949), and male (AOR: 1.074, 95% CI: 1.053–1.095), mothers had lower BMI (AOR: 1.543, 95% CI: 1.492–1.595), mothers who had no education (AOR: 1.595, 95% CI: 11.532–1.662), belongs to poorest wealth index (AOR: 1.857, 95% CI: 1.766–1.952), and the children belong to the household with unhygienic satiation practices (AOR: 1.097, 95% CI: 1.070–1.123) were more likely to be stunted. The decomposition results revealed that the variables included in the study could explain 68.9% of the stunting inequality between SC-ST and non-SC-ST groups. The household’s wealth index is found to be a leading factor, which contributed nearly 41.3% of total stunting inequality exists between these two groups, followed by mothers’ education (12.86%) and mothers’ BMI (11.02%), sanitation facilities (4.26%), children’s birth order (3.32%) and mother’s type of delivery (1.49%). These findings emphasize the importance of targeted interventions. Prioritizing policies that address household economic enhancement, women’s education and empowerment can be instrumental in reducing social group inequality and lowering the overall prevalence of stunting. Ensuring access to improved hygienic sanitation facilities in the household is equally important for achieving better health outcomes for the children.